Sarcoidosis Following Hematopoietic Stem Cell Transplantation: Clinical Characteristics and HLA Associations - Wurm-Kuczera, Rebecca Isabel; Buentzel, Judith; Koenig, Julia Felicitas Leni; Legler, Tobias; Valk, Jan-Jakob; Hasenkamp, Justin; Jung, Wolfram; Rademacher, Jan-Gerd; Korsten, Peter; Wulf, Gerald Georg (Frontiers in Immunology, 2021)
Purpose: Extrinsic factors and genetic predisposition contribute to the etiology of sarcoidosis, converging in a phenotype of altered immune response associated with multisystemic inflammatory granulomatous tissue infiltration. Immunological reconstitution after hematopoietic stem cell transplantation (HSCT) may represent a unique window for the pathogenesis of the disease. We describe the incidence, clinicopathological features, and HLA associations of sarcoidosis after HSCT in a single-center cohort of patients, together with data from previously published cases. Methods: We retrospectively analyzed clinical characteristics and HLA haplotypes from allogeneic (allo) or autologous (auto) HSCT patients from January 2001 through May 2021 at the University Medicine Goettingen (UMG), and data from 15 previously published cases. Results: A total number of 19 patients was identified. These included four patients from our center (three allo HSCT, one auto HSCT) and 15 patients from the literature review. Thirteen patients had received an allo HSCT, and six patients had an auto HSCT. Sarcoidosis occurred after a median interval of 20 (after allo HSCT) and 7 (after auto HSCT) months, respectively. The predominant HLA allele associated with sarcoidosis was HLA DRB1*03:01. Sarcoidosis involved the respiratory tract in 15 patients (three unknown, one without pulmonary involvement), and it was associated with graft-versus-host disease in seven of 13 patients receiving allo HSCT. None of the donors or patients had a history of sarcoidosis before transplantation. Disease manifestations resolved with standard glucocorticoid treatment without long-term sequelae. Conclusion: Sarcoidosis may occur at low frequency during reconstitution of the immune system after HSCT. HLA allele associations reflect the associations observed in the general population, particularly with DRB1*03:01. Further insights into the interplay between T cell reconstitution and the development of sarcoidosis could also provide novel approaches to an improved understanding of the pathogenesis in sarcoidosis.